Language use in the classroom: Identity in classroom discourse - Muhlisin, Muhlisin (Universitas Muhammadiyah Jember, 2017)
AbstractThis study concerned group of Indonesian EFL learnersâ€™ perceptions regarding the use of Indonesian (L1) and English language (L2) by their teachers in the classroom. In particular, the study aimed to unravel how these learners perceived the use of their L1 and L2 during the course of English instruction in the classroom and how their perceptions might have been shaped by different aspects of â€œidentity constructionâ€ to which they were oriented. Data were gathered through administering a questionnaire to one hundred seventy-three adult Indonesian EFL learners. Analysis of the learnersâ€™ responses suggested that they maintained different perceptions with regard to the use of their L1 and L2 and that their perceptions may be subsumed into two broad categories, each of which reflects the differences in their perceptions. Factors that might have affected the learnersâ€™ perceptions were then critically discussed in the light of identity theory in the context of L2 pedagogy. In particular, the theory suggests that different aspects of identity construction to which learners are oriented affect their perceptions of the use of theirL1 and L2 in the classroom. Further, these different aspects of identity construction may also affect how learners are likely to respond to the use of an L1 and L2 in the classroom (and beyond).Keywords: English as a foreign language (EFL), language use, identity theory in L2 pedagogy